2010
DOI: 10.1111/j.1365-2486.2010.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Overfishing of top predators eroded the resilience of the Black Sea system regardless of the climate and anthropogenic conditions

Abstract: It is well known that human activities, such as harvesting, have had major direct effects on marine ecosystems. However, it is far less acknowledged that human activities in the surroundings might have important effects on marine systems. There is growing evidence suggesting that major reorganization (i.e., a regime shift) is a common feature in the temporal evolution of a marine system. Here we show, and quantify, the interaction of human activities (nutrient upload) with a favourable climate (run-off) and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 41 publications
1
95
0
Order By: Relevance
“…The dominant signals were modeled using Generalized Additive Models in fully additive (GAM) and also a threshold (tGAM) formulation (18,19) that allows for changes in the relationship between a response term and an explanatory variable as a function of another variable. The models were used to hindcast the data and to conduct simulations under scenarios of external forcing based only on the initial conditions of each food web component.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The dominant signals were modeled using Generalized Additive Models in fully additive (GAM) and also a threshold (tGAM) formulation (18,19) that allows for changes in the relationship between a response term and an explanatory variable as a function of another variable. The models were used to hindcast the data and to conduct simulations under scenarios of external forcing based only on the initial conditions of each food web component.…”
Section: Significancementioning
confidence: 99%
“…To address this question, an advanced statistical modeling approach (18,19) was developed incorporating the interactions between three phytoplankton measures (abundance of diatoms and dinoflagellates and a greenness index), three zooplankton groups (the large copepods Calanus finmarchicus and Calanus helgolandicus as well as an assemblage of small copepod species), four forage fish species (herring, sprat, sandeel, and Norway pout), four piscivorous fish species (cod, haddock, whiting, and saithe), and one seabird group. The model incorporates direct and indirect responses of these groups to…”
mentioning
confidence: 99%
“…The overfishing of the pelagic top predators in the 1970s and of planktivorous fish in the 1990s resulted in regime shifts and caused changes in the abundance of the zooplankton, jellyfish, and phytoplankton, as well as in surface oxygen and phosphate concentrations. Llope et al (2011) identified the removal of top predators as a key element in terms of loss of resilience that inevitably leads to reorganization of the food web. Historically, the fishery-driven trophic cascade first disturbed the structure of the system from higher trophic levels and then the already disturbed food web was further degraded by eutrophication.…”
Section: Eutrophication and Fisheries In The Black Seamentioning
confidence: 99%
“…Historically, the fishery-driven trophic cascade first disturbed the structure of the system from higher trophic levels and then the already disturbed food web was further degraded by eutrophication. Simulation results demonstrated that increased productivity could have been more efficiently handled by a more complex ecosystem including viable top predators (Llope et al 2011). For that reason, a regeneration of the food web structure by rebuilding the top predator stocks could improve the system's ability to counterbalance fluctuations driven by climate or eutrophication.…”
Section: Eutrophication and Fisheries In The Black Seamentioning
confidence: 99%
“…Fisheries scientists suggest that perhaps 70% of the harbor porpoise population in the Black Sea has already been lost through direct and indirect effects (8). With the concomitant loss of top predators in the Black Sea ecosystem, the short-beaked common dolphin (Delphinus delphis) and the common bottlenose dolphin (Tursiops truncatus), reversing a regime shift now may not even be possible (9,10).…”
mentioning
confidence: 99%